Perencanaan Komposisi Campuran Base dengan Menggunakan Limbah Cangkang, Bottom Ash, dan Fly Ash - Chandra, Jaliusman; Abdillah, Nuryasin; Abrar, Aidil (SLUMP TeS : Jurnal Teknik Sipil, 2024)
Fly ash and bottom ash (FABA) are materials produced from the use of coal as fuel for steam power plants, which is one of the sources of electricity generation in Indonesia. This study aims to map the physical properties of fly ash and bottom ash (FABA) mixed with ordinary heap soil as well as the chemical properties of FABA. This research was conducted in the laboratory, by testing the physical properties of the original soil and the original soil mixture with FABA in variations of the FABA addition mixture of 65%, 10% and 25%From the results of the study, the results obtained from the physical properties of the original soil based on the AASHTO method are included in soil types A-7-6, based on the USCS method, they are included in OL, namely organic silt and organic silt clay with moderate plasticity and based on the USDA method, they are included in silt clay. For the addition of fly ash and bottom ash (FABA) to the original soil, it was found that the higher the percentage of fly ash and bottom ash (FABA) to the total weight of the original soil showed an increase in optimum water content and maximum dry density tended to decrease and could change the category of soil grouping. Utilization of FABA as an additive can increase the carrying capacity of ordinary embankments.